Clinico-Demographic Characteristics and Factors Associated with Migraine of Children: A Study in a Referral Neurologic Centre of Bangladesh - Mistry, Banita; Ara Begum, Most Shameem; Chowdhury, Yamin Shahriar; Mistry, Palash Kanti; Saha, Dipa; Parvin, Joboida; Chandra, Mahua (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Migraine is one of the most common neurologic conditions in children .Migraine is the commonest cause of severe recurrent headache in children. Clinical presentations of migraine vary according to patient age. Objective: To study demographic, clinical profile and factors associated with migraine of children in outpatient department of a referral neurologic hospital. Methodology: This was a cross-sectional study carried out at the outpatient department of Paediatric Neurology, National Institute of Neurosciences & Hospital (NINS), Dhaka from January to July, 2018. Children of 5-15 years of migraine with / without aura of severe / moderate intensity were included to document demographic, clinical profile and factors influencing migraine. Result: Most of the patients were in the age group of 10-14 years 57 (71.25%). Children of both sexes are almost equally suffered from migraine (M vs F, 51.25% vs 48.75%).Most of the children had ³5 attacks/month. Unilateral headache (55%) was more common than bilateral (45%). Regarding quality of pain aching pain (53.75%) was more prevalent followed by tightening 18.75%, pulsating 17.5%. Aura was present in 27.5%. Nausea was present in 67.5% but vomiting was only in 32% patients. 65% patients had photophobia. Among patients 65% had family history of migraine. 86% patients took abortive drugs during attack. Bright sunshine was the most common precipitating factors for migraine attack followed by stress 37%. Most of the patients relieved from pain by taking rest (78%). Conclusion: Migraine was more common in late childhood and early teen age. Boys and girls were almost equally affected. Most common clinical findings were unilateral aching pain, nausea and photophobia. Bright sunshine, stress are the most common aggravating factors for migraine. J Shaheed Suhrawardy Med Coll 2021; 13(2): 91-93